Artificial Intelligence in Indonesian Ports: Opportunities and Challenges - Safuan; Syafira, Asma (Transactions on Maritime Science, 2024)
The primary objective of this study is to ascertain the potential advantages and obstacles associated with implementing artificial intelligence (AI) within the context of Indonesian ports. The study utilises qualitative methodologies, namely conducting in-depth interviews with port managers, technicians, and operational staff. Additionally, it involves the analysis of secondary data derived from yearly port reports, case studies, and academic literature. The findings demonstrate that artificial intelligence (AI) can augment operational efficiency, boost ship traffic management, and automate container handling activities within Indonesian ports. Nevertheless, integrating artificial intelligence (AI) within Indonesian ports is currently in its nascent phase, encountering challenges about physical limitations, human capital, and regulatory frameworks. The investigation also examines using interconnected technologies, including the Internet of Things (IoT), blockchain, and augmented reality (AR), to provide additional advantages to the port sector. In summary, via a comprehensive comprehension and effective utilisation of the opportunities afforded by artificial intelligence (AI), Indonesian ports have the potential to position themselves as frontrunners in the international maritime sector.